2012
DOI: 10.1371/journal.pone.0034534
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Dysregulation in the Spinal Cord following Traumatic Injury

Abstract: Spinal cord injury (SCI) triggers a multitude of pathophysiological events that are tightly regulated by the expression levels of specific genes. Recent studies suggest that changes in gene expression following neural injury can result from the dysregulation of microRNAs, short non-coding RNA molecules that repress the translation of target mRNA. To understand the mechanisms underlying gene alterations following SCI, we analyzed the microRNA expression patterns at different time points following rat spinal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
175
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(188 citation statements)
references
References 155 publications
13
175
0
Order By: Relevance
“…In addition to MLK3, possible targets of miR-138 also include apoptosis-related genes like caspase-3, calpain 1, calpain 2, Bcl-2, c-Myc, and apoptosis-inducing factor (AIF) (8,25). Some of these target genes were reported to be involved in the pathological process of SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to MLK3, possible targets of miR-138 also include apoptosis-related genes like caspase-3, calpain 1, calpain 2, Bcl-2, c-Myc, and apoptosis-inducing factor (AIF) (8,25). Some of these target genes were reported to be involved in the pathological process of SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of the miRNAs in SCI development and their value in SCI diagnosis were reported in several papers (5)(6)(7). The microarray analysis revealed that miR-138 expression was signifi cantly enriched in the adult rat spinal cord following SCI (8). Mixed-lineage kinase 3 (MLK3) contains seeding sequences of miR-138 in its 3'-untransltaed region (UTR) and was proved to be a direct target of miR-138 (9).…”
Section: Introductionmentioning
confidence: 99%
“…11 After spinal cord injury in Wistar rats, miRNA expression is markedly subdued from day 3 after injury with gradual rebound of down-regulated miRNA at 7 days after injury. 12 Suppression of miRNA expression after spinal cord injury was verified in an independent study in which downregulated miRNAs were reported up to 14 days after injury. 13 The pattern of miRNA suppression after injury holds across organ systems.…”
Section: Development Is the Key To Regenerationmentioning
confidence: 90%
“…A number of microRNAs were found in the mammalian brain and spinal cord, where they are involved in the regulation of several nervous diseases (1). Recently, several reports have revealed important roles of microRNAs in traumatic SCI (2,3). We here describe for the first time microRNA expression profiling of ischemic rat spinal cord in the context of pre-treatment with atorvastatin using a quantitative real-time PCR based array.…”
Section: Short Communicationmentioning
confidence: 99%